Financial Soundness Indicators and Banking Crises - Costa Navajas, Matias; Thegeya, Aaron (Washington, D.C. : International Monetary Fund, 2013)
The paper tests the effectiveness of financial soundness indicators (FSIs) as harbingers of banking crises, using multivariate logit models to see whether FSIs, broad macroeconomic indicators, and institutional indicators can indeed predict crisis occurrences. The analysis draws upon a data set of homogeneous indicators comparable across countries over the period 2005 to 2012, leveraging the IMF's FSI database. Results indicate significant correlation between some FSIs and the occurrence of systemic banking crises, and suggest that some indicators are precursors to the occurrence of banking crises.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet